Character Education In Developing Students At Sma Negeri 6 Palembang - Mulyati, Sry; Fitria, Happy; Wahidy, Achmad (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This research aims to identify and describe the implementation of character education in developing students at SMA Negeri 6 Palembang. This research is a qualitative descriptive study with a phenomenological study approach. Sources of data were obtained from the principal, deputy principal of the IMTAQ school, teachers and students. Data collectionused was observation, interviews, and documentation. The results showed that the implementation of character education in developing students at SMA Negeri 6 Palembang was integrated into imtaq activities, namely online morning tausiah, online men and women’s affairs activities, which achieved good results. Success can be seen from the attitudes and behavior of students as reflected on the results of the observation sheet in the form of religious attitudes, honesty, discipline and independence. The average achievement score of students' answers on the behavior